2023
DOI: 10.3389/fphys.2023.1103141
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctanoic acid (PFOA) exposure in relation to the kidneys: A review of current available literature

Abstract: Perfluorooctanoic acid is an artificial and non-degradable chemical. It is widely used due to its stable nature. It can enter the human body through food, drinking water, inhalation of household dust and contact with products containing perfluorooctanoic acid. It accumulates in the human body, causing potential harmful effects on human health. Based on the biodegradability and bioaccumulation of perfluorooctanoic acid in the human body, there are increasing concerns about the adverse effects of perfluorooctano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 180 publications
0
7
0
Order By: Relevance
“…In vitro studies are recommended to well-known the impact of long-term PFOA exposure on the kidney including the toxicological information and mechanism of toxicity under stressed conditions (54,55) In conclusion, after 4 weeks, positive associations of PFOA with serum creatinine, have been observed in nondiabetic and diabetic guinea pigs exposed to PFOA. Furthermore, PFOA lead to disturbances in the kidney performance and nephrotoxicity in diabetic and nondiabetic animals.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In vitro studies are recommended to well-known the impact of long-term PFOA exposure on the kidney including the toxicological information and mechanism of toxicity under stressed conditions (54,55) In conclusion, after 4 weeks, positive associations of PFOA with serum creatinine, have been observed in nondiabetic and diabetic guinea pigs exposed to PFOA. Furthermore, PFOA lead to disturbances in the kidney performance and nephrotoxicity in diabetic and nondiabetic animals.…”
Section: Discussionmentioning
confidence: 92%
“…increase in concern about the potential harmful effects of PFOA and its salts on both the environment and living organisms (9,10). Researchers revealed that PFOA accumulate mainly in the kidney and causes nephrotoxicity with impairment kidney functions (6). Moreover, diabetes (DM) is one of the health conditions which can be caused by Perfluorooctanoic acid (PFOA) (11).…”
Section: Al-aaraje Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Irrespective of how albumin can transit across the endothelial (e.g., transcytosis) and basement membrane barriers, it can be internalized by podocytes, partially bypassing the filtration slit diaphragm through transcytosis [ 77 ], allowing PFOA to enter the cells that are critical for maintenance of the morphofunctional integrity of the glomerular filtration barrier. Moreover, in humans, PFOA is known to be filtered freely in the glomerulus, actively excreted in the proximal tubule, and then readsorbed by organic anion transport (OAT) peptides [ 78 , 79 ]. Interestingly, in the mouse, kidney OAT-like peptides have been described in blood vessels, parietal epithelial cells, podocytes, distal convoluted tubules, connecting tubules, and collecting tubules [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kidneys are one organ in the body that has been shown to be impacted by the presence of PFOA. A review written by Liu et al, [34], states that kidneys are recognized as a target organ for PFOA due to their ability to bind to proteins and accumulates in organs. Glomerular filtration is an important function performed in the kidneys that help filter blood and play a role in the excretion of certain compounds in the body.…”
Section: Impact On Kidneys and Other Health Impactsmentioning
confidence: 99%